Ice castles [videorecording (DVD)] - Wrye, Donald; Firth, Taylor, 1991-; Mayes, Rob; Czerny, Henry; Oberstar, Molly; Kwan, Michelle, 1980- (Sony Pictures Home Entertainment, 2010)
Alex Winston is young, beautiful and talented. She comes from nowhere to become a figure skating superstar. She has to push herself, reinvent herself, and most painfully of all, leave her boyfriend behind. When a tragic fall leaves her blind, she needs someone to believe in her, to love her and convince her she has the strength to skate and dream again.